Safety Induction as an Effort to Improve School Safety Standards - Evi Widowati; Anik Wahyuningsih; Andhi Wijayanto; Palgunadi Palgunadi; Adelia Oktafiani; Rafidha Alifah; Della Fitriana; Alifia Fairuzahra; Fransiska Dwiyandari (Universitas Negeri Semarang, 2026)
Schools are vulnerable to disasters, especially elementary schools, because most of the children there lack the skills needed to respond to disasters.. The identification revealed that elementary school Y is a school with a large student population but a building with a high risk of hazards, both in terms of construction and environmental hazards and fire hazards. This school has begun implementing a school safety system in the initial stages, including the installation of simple safety infrastructure. However, in terms of human resource organization, improvements are still needed, as the school is not yet able to organize its members, especially students, during emergencies. Furthermore, the student population is highly dynamic, with student turnover occurring annually. This requires schools to conduct disaster simulations regularly throughout the year to enhance the preparedness of the school community. Real-world conditions indicate that schools are not yet adequately equipped to organize large crowds during emergencies and do not yet have standard safety induction materials that can be used consistently to train all students in disaster preparedness in responding to hazards. The community service activity produced a school disaster mitigation pocket book that can be used as a safety induction media for its residents, and the training results showed an increase in pre-test and post-test scores by 22%. In addition, the results of the evacuation simulation practice showed that the total time required was only 1 minute 51.75 seconds for all students to be present at the assembly point. This indicates an increase in students' understanding and preparedness in responding to emergencies. This activity supports the achievement of Asta Cita 4 and Sustainable Development Goals, especially goal 3 (Good Health and Well-being) and goal 11 (Sustainable Cities and Communities).